The mental health service use and undetected PTSD among psychiatric patients in tertiary care - Jóel Dan Nielsen Björnsson 1994- (2020)
Over the past two decades research has demonstrated evidence for high estimates of posttraumatic stress disorder (PTSD) among mental health patients. It is troublesome that studies have found that assessment of trauma and PTSD among patients is lacking, leading to low detection rates and inadequate treatment in mental health care systems. Undetected PTSD is associated with increased mental health service use, particularly of more expensive services such as hospitalizations and acute psychiatric care. Undiagnosed PTSD has been found to worsen patient prognosis in comorbid mental disorders and increase relapses in their illness, which ultimately increases the burden on psychiatric care. The aim of the current study was to explore whether there are significant differences in the mental health service use between psychiatric patients that meet criteria for PTSD and those that do not. Furthermore, we examined prevalence rates of undetected PTSD to assess the extent of underdiagnosis. Participants were 230 adults (157 women, 70 men, and 3 other) aged 18-69 years, currently seeking mental health services within the psychiatric services of Landspitali – The National University Hospital of Iceland, between April 2018 and December 2019. The results demonstrate that the average score on the PCL-5 was 37.9 in our sample, and that 122 (60%) participants met criteria for PTSD based on the cut-off score on the PCL-5 (≥33). Of those that met criteria for PTSD, only 12.3% had a documented diagnosis of trauma and stressor-related disorder. Participants meeting criteria for PTSD had more service periods in their mental health service utilization and they had more contacts with the psychiatric emergency room, compared to patients not meeting PTSD criteria. The findings underscore the importance of screening and diagnostic procedures for trauma and PTSD in tertiary care, especially in psychiatric acute care settings. If improved, it may lead to better detection rates of true positive cases of PTSD, followed by more accurate ...